Accessibility of Persons with Disabilities in the Review of Disability Fiqh - Puji Lestari; Raodah Raodah (Santri: Journal of Pesantren and Fiqh Sosial, 2020)
Accessibility is a form of sympathy and empathy to provide convenience to persons with disabilities by providing friendly public facilities. This study aims to explain how the physical facilities provided by the Pesantren Institute Mathali'ul Falah (IPMAFA) Pati in accommodating people with disabilities in learning and the application of religious fiqh with disabilities. This research is focused on physical facilities in the form of stairs, ramps, doors, classrooms, chairs, tables, laboratories, libraries, toilets, showers, and mosques. This research is qualitative research with descriptive analysis, data collection using observation, interviews, and documentation. Data analysis was carried out by comparing the results of field data with the standards for accessibility of public facilities set by the Ministry of Public Works and disability fiqh. From the results of this study, it was found that IPMAFA had prepared friendly facilities for persons with disabilities however accessibility of facilities is not yet fully adequate and disability-friendly for disabled people who use canes, crutches, and wheelchairs. Facilities that are classified as disability-friendly include stairs, doors, classrooms, tables and chairs, libraries, and laboratories. In the disability fiqh review, the accessibility of taharah, wudhu, and prayer facilities at the IPMAFA is not yet suitable for people with disabilities, whether users of sticks, crutches, or wheelchairs. The results of this study can be a reference for the IPMAFA campus in realizing a disability-friendly campus.